2009
DOI: 10.1186/1471-2164-10-343
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in mouse embryo fibroblasts lacking stathmin, a microtubule regulatory protein, reveal changes in the expression of genes contributing to cell motility

Abstract: Background: Stathmin (STMN1) protein functions to regulate assembly of the microtubule cytoskeleton by destabilizing microtubule polymers. Stathmin over-expression has been correlated with cancer stage progression, while stathmin depletion leads to death of some cancer cell lines in culture. In contrast, stathmin-null mice are viable with minor axonopathies and loss of innate fear response. Several stathmin binding partners, in addition to tubulin, have been shown to affect cell motility in culture. To expand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A comparison of STMN1 +/+ vs. STMN1 -/- mouse embryonic fibroblasts identified motor proteins as the largest group of genes with altered expression profiles. Interestingly, while differential expression of 13 kinesin motor subunits was detected alteration in dynein motor subunit expression was not observed, and only 5 genes encoding dynein light or intermediate chains showed altered expression [59]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of STMN1 +/+ vs. STMN1 -/- mouse embryonic fibroblasts identified motor proteins as the largest group of genes with altered expression profiles. Interestingly, while differential expression of 13 kinesin motor subunits was detected alteration in dynein motor subunit expression was not observed, and only 5 genes encoding dynein light or intermediate chains showed altered expression [59]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in studies performed in vertebrate model systems the function of only one member of the stai family is altered, and genetic redundancy by the remaining stathmin-like proteins may compensate and account for the observed phenotypic differences. Indeed, it has been reported in STMN1 knockout MEFs that the expression of STMN2 is decreased and STMN4 is increased [59], while in STMN1 knockout mice, an increase in the expression of STMN3 and STMN4 is observed [64,73]. The stai protein has two known activities; a MT depolymerizing activity as well as a tubulin binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, cells differing in p53 status could be dissimilar in more general ways that subsequently impact the degree of MT stability observed after stathmin depletion. For example, a large number of gene expression changes have been noted after depletion or knockout of either stathmin or p53 (Ringhoff and Cassimeris 2009a; Sur et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Moderate pathological defects only 682 appear in adult mice, with a mildly impaired LTP in the cortico-and 683 thalamo-amygdala pathways leading to fear memory behavioral 684 deficits(Shumyatsky et al, 2005), and in aging animals which 685 develop a mild central and peripheral axonopathy(Liedtke et al, 686 2002). The absence of developmental phenotype might be due 687 likely to some compensatory mechanisms, as an increased level of 688 stathmin 3 has been detected in mice lacking stathmin 1(Liedtke 689 et al, 2002), and the expression of stathmin 2 is decreased and that 690 of stathmin 4 is increased in stathmin 1 knock-out mouse 691 embryonic fibroblasts(Ringhoff and Cassimeris, 2009). Gene 692 expression profiles have also revealed that the expression of 693 tubulin isotypes is altered in stmn1 À/À mouse embryonic 694 fibroblasts(Ringhoff and Cassimeris, 2009), indicating that 695 stathmin 1 plays a role also in the maintenance of the tubulin 696 pool diversity.…”
mentioning
confidence: 96%
“…The absence of developmental phenotype might be due 687 likely to some compensatory mechanisms, as an increased level of 688 stathmin 3 has been detected in mice lacking stathmin 1(Liedtke 689 et al, 2002), and the expression of stathmin 2 is decreased and that 690 of stathmin 4 is increased in stathmin 1 knock-out mouse 691 embryonic fibroblasts(Ringhoff and Cassimeris, 2009). Gene 692 expression profiles have also revealed that the expression of 693 tubulin isotypes is altered in stmn1 À/À mouse embryonic 694 fibroblasts(Ringhoff and Cassimeris, 2009), indicating that 695 stathmin 1 plays a role also in the maintenance of the tubulin 696 pool diversity. It has been suggested recently that stathmin 697 invalidation reduces the number of neural progenitor cells and 698 favors the transition from dividing to differentiated neurons in the 699 adult hippocampus(Boekhoorn et al, 2014).700 The recently developed heterozygous stathmin 2, 3 or 4 or 701 homozygous stathmin 3 or 4 knock-out mice (Sobel and Devignot 702 unpublished) breed and develop normally, and display no easily 703 detected and significant anatomical, physiological or behavioral 704 abnormalities.…”
mentioning
confidence: 96%